Pengaruh Konsentrasi Kalsium Klorida pada Viabilitas dan Daya Sweelling Beads Enkapsulasi Paenibacillus polymyxa secara In Vitro - Sari, Zulfa Novita; Nirwanto, Hery; Lestari, Safira Rizka (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: Paenibacillus polymyxa is a potent antagonist that can be utilized as a biological agent. The use of biological agents has gained interest among farmers, but their application in liquid formulations has not consistently maintained the optimal stability and viability of microorganisms. One promising approach to overcome this problem is bioencapsulation, which is a method of wrapping biological agents to protect bacteria in the soil and increase their efficiency. This study aims to assess the encapsulation efficiency, measure the viability of microorganisms in the beads, and determine the difference in swelling power of beads made with various concentrations of calcium chloride (CaCl2) as a binding agent. Method: Beads were produced using the extrusion method by combining Paenibacillus polymyxa suspension, sodium alginate suspension, and adding CaCl2 at concentrations of 1%, 3%, and 5%. Results: The results showed that different CaCl2 concentrations can affect the viability of Paenibacillus polymyxa in beads. Beads made with CaCl2 at 3% concentration were the best results in the encapsulation efficiency test compared to beads made with 1% and 5% CaCl2 binders. In comparison, beads with 3% and 5% CaCl2 concentrations were able to maintain the viability of microorganisms at a higher level and for a longer time than beads using CaCl2 at 1% concentration. The decrease in viability and swelling power of the beads is thought to be caused by the carrier material used and the storage conditions. Conclusion: Bead treatment with 3% calcium chloride concentration was the best treatment for encapsulation efficiency in absorbing Paenibacillus polymyxa, amounting to 98.21%.